Increased MxA protein expression and dendritic cells in spongiotic dermatitis differentiates dermatomyositis from eczema in a single‐center case‐control study. (23rd October 2020) - Zeidi, Majid; Chen, Kristen L.; Patel, Basil; Ravishankar, Adarsh; Lim, Rachel; Werth, Victoria P.
Abstract: Background: Dermatomyositis (DM) is conventionally characterized by interface dermatitis (ID) on skin histopathology. A subset of DM patients has skin biopsies showing spongiotic dermatitis (SD), a histopathology more commonly seen in eczema. In this study, we aimed to (a) identify the percentage of clinically diagnosed DM patients with SD skin biopsies, (b) identify cytokine and cell markers that can help determine if a SD skin biopsy is consistent with DM. Methods: In this case‐control study, biopsy specimens from ten DM patients with SD (DM‐SD) were compared to specimens from ten healthy controls, ten patients with eczema, and 12 patients with DM with ID (DM‐ID). Specimens were stained by immunohistochemistry for MxA, IFN‐β, CD11c, and BDCA2. One‐way ANOVA with Bonferroni's multiple comparison test was used to compare protein expression between groups. Results: Eleven of 164 (6.7%) patients with a clinical diagnosis of DM at our tertiary care center were identified as having SD. MxA, IFN‐β, CD11c, and BDCA2 protein expression was significantly higher in DM‐SD compared to eczema and healthy controls. Expressions of MxA, IFN‐β, and BDCA2 were not significantly different between DM‐SD and DM‐ID. Conclusion: Increased MxA, IFN‐β, CD11c, and BDCA2 protein expression may aid in distinguishing between DM‐SD and eczema and warrants further investigation.